2021
DOI: 10.1042/bcj20200542
|View full text |Cite
|
Sign up to set email alerts
|

Complexin-2 redistributes to the membrane of muscle cells in response to insulin and contributes to GLUT4 translocation

Abstract: Insulin stimulates glucose uptake in muscle cells by rapidly redistributing vesicles containing GLUT4 glucose transporters from intracellular compartments to the plasma membrane (PM). GLUT4 vesicle fusion requires the formation of SNARE complexes between vesicular VAMP and PM syntaxin4 and SNAP23. SNARE accessory proteins usually regulate vesicle fusion processes. Complexins aide in neuro-secretory vesicle-membrane fusion by stabilizing trans-SNARE complexes but their participation in GLUT4 vesicle fusion is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 71 publications
(107 reference statements)
0
11
0
1
Order By: Relevance
“…The complexin proteins were first identified as regulatory proteins involved in synaptic vesicle exocytosis in neurons ( 153 , 154 ). Recently, the expression of complexin-2 was also identified in skeletal muscle cells ( 62 ). Complexins contain an N-terminal accessory helix and a central helix, which interacts with the ternary SNARE complex in a calcium-dependent manner ( 155 , 156 ).…”
Section: The Physiologic and Mechanistic Roles Of Snares In Glut4 Ves...mentioning
confidence: 99%
See 3 more Smart Citations
“…The complexin proteins were first identified as regulatory proteins involved in synaptic vesicle exocytosis in neurons ( 153 , 154 ). Recently, the expression of complexin-2 was also identified in skeletal muscle cells ( 62 ). Complexins contain an N-terminal accessory helix and a central helix, which interacts with the ternary SNARE complex in a calcium-dependent manner ( 155 , 156 ).…”
Section: The Physiologic and Mechanistic Roles Of Snares In Glut4 Ves...mentioning
confidence: 99%
“…Complexins contain an N-terminal accessory helix and a central helix, which interacts with the ternary SNARE complex in a calcium-dependent manner ( 155 , 156 ). In skeletal muscle cells, complexin-2 translocates to the PM via the insulin-induced activation of the Rho-family GTPase Rac1 in the noncanonical insulin signaling pathway ( 62 ). Depletion of complexin-2 using siRNA inhibits insulin-stimulated GLUT4 accumulation at the L6 GLUT4myc myoblast surface ( 62 ), but overexpression of complexin-2 also impairs insulin-stimulated GLUT4 translocation ( 62 ).…”
Section: The Physiologic and Mechanistic Roles Of Snares In Glut4 Ves...mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, type 2 diabetes (T2D) is characterised by an impaired glucose uptake in insulinsensitive tissues such as in muscles with, as consequences, hyperglycaemia and glucotoxicity [1]. In this context, the recent study of Pavarotti et al [2] is important as it identified a new actor, complexin-2, regulating the insulin-mediated translocation of glucose transporter 4 (GLUT4) to the plasma membrane (PM) in skeletal muscle.…”
mentioning
confidence: 99%